Analisa Geometrik Polihedron Platonik Solid - Iyus S Sanusi (Aliansi Desainer Produk Industri Indonesia (ADPII), 2019)
In science the term polyhedron visually is a 3-dimensional geometric form which contains elements of constructive logic, space, form, angle and lines and the logic of viewpoints that can be learned to develop an idea of the shape of a design.Platonic Polyhedron Solid is a regular geometric form of polyhedron consisting of tetrahedrons, hexahedrons, octahedrons, dodecahedron and icosahedron. These five Platonic Solid Polyhedrons have the characteristics formed from 3 types of regular polygons, namely trigon, tetrahedron and pentagon.In this paper the author tries to analyze the structure of the geometric shape of a solid platonic polyhedron to find out if one solid platonic polyhedron is combined with one another, for the purpose of knowing the possibilities and variants of novelty that can be obtained. In its implementation it uses the experimental method through modeling polyhedron geometric shapes and drawing constructive geometric shapes through 2D and 3D image media.The output of the results of this geometric analysis is expected to be able to obtain references that can be used as teaching materials for the geometric foundations of polyhedron and can be used as a formulation of initial ideas in finding design ideas that are specifically based on geometric shapes of polyhedrons.Keywords: Solid Platonic, Polyhedron, Comparison Ratio, Geometric Shape ABSTRAKDalam ilmu pengetahuan istilah polihedron secara visual merupakan suatu bentuk geometrik 3 dimensi yang didalamnya terkandung unsur logika konstruktif , ruang, bentuk, sudut dan garis serta logika sudut pandang yang dapat dipelajari untuk pengembangan suatu gagasan bentuk dari suatu desain.Polihedron Platonik Solid merupakan bentuk geometrik polihedron reguler yang terdiri dari tetrahedron, heksahedron, oktahedron, dodecahedron dan icosahedron. Kelima polihedron Platonik Solid ini memiliki ciri terbentuk dari 3 jenis poligon reguler yaitu trigon, tetrahedron dan pentagon.Dalam tulisan ini penulis mencoba menganalisa struktur bentuk geometris polihedron platonik solid untuk mengetahui jika polihedron platonik solid yang satu dengan yang lainnya dikombinasikan, untuk tujuan mengetahui kemungkinan dan varian kebaruan yang dapat diperoleh. Dalam implementasinya menggunakan metode eksperimen melalui pembuatan model bentuk geometris polihedron dan menggambar konstruktif bentuk geometris melalui media gambar 2D dan 3D.Luaran dari hasil analisa geometris ini diharapkan dapat diperoleh acuan-acuan yang dapat menjadi bahan ajar dasar-dasar geometris polihedron dan dapat dipergunakan sebagai formulasi gagasan awal dalam menemukan gagasan desain yang khususnya berbasis bentuk geometris polihedron .Kata kunci: Polihedron Platonik Solid, Rasio Perbandingan, Bentuk Geometris